Pengaruh Kinerja Keuangan, Intensitas Aset Tetap dan Sales Growh Terhadap Tax Avoidance - Imas PrasTika; Syamsul Mu arif (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to determine the effect of Financial Performance, Fixed Asset Intensity and Sales Growth on Tax Avoidance. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period with a population of 82 companies. The sample used in this research was determined using a purposive sampling technique, resulting in a sample of 11 companies and 55 observation data. Hypothesis testing is carried out using the E-views 12 application. The data analysis technique used in data research is multiple linier analysis. Based on the test result in the F test, simultaneously Financial Performance, Fixed Asset Intensity and Sales Growth influence Tax Avoidance. Meanwhile, the test results of the T test partially state that Financial Performance has a effect on Tax Avoidance, Fixed Asset Intensity has a effect on Tax Avoidance, and Sales Growth has a effect on Tax Avoidance.